Kebutuhan Air Kelapa Sawit dan Domestik pada Wilayah Perkebunan Kelapa Sawit Binturung Estate Kecamatan Pamukan Utara Kalimantan Selatan - Novrianti Veranica (Anterior Jurnal, 2014)
Less than optimal use of water management in oil palm plantations "Binturung Estate" as a result of lack of maintenance of the water system konfisi. Increased water demand with increasing population and water demand on palm oil plants, less frequentlymet during the dry seasonis long enough. To meetthe needs of a need to work with to make ponds and calculate the volume of water that can be accommodated. From the calculation of the volume of water that can be accommodated for an area of 42,000 km2, storage ponds for 0,0360 m3/sec>volume of water need sof 0.00057m3/s.